AHR Regulates NK Cell Migration via ASB2–Mediated Ubiquitination of Filamin A - Shin, June Ho; Moreno-Nieves, Uriel Y.; Zhang, Luhua H.; Chen, Chen; Dixon, Amera L.; Linde, Miles H.; Mace, Emily M.; Sunwoo, John B. (Frontiers in Immunology, 2021)
Natural killer (NK) cells are effector cells of the innate immune system involved in defense against virus-infected and transformed cells. The effector function of NK cells is linked to their ability to migrate to sites of inflammation or damage. Therefore, understanding the factors regulating NK cell migration is of substantial interest. Here, we show that in the absence of aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, NK cells have reduced capacity to migrate and infiltrate tumors in vivo. Analysis of differentially expressed genes revealed that ankyrin repeat and SOCS Box containing 2 (Asb2) expression was dramatically decreased in Ahr–/– NK cells and that AhR ligands modulated its expression. Further, AhR directly regulated the promoter region of the Asb2 gene. Similar to what was observed with murine Ahr–/– NK cells, ASB2 knockdown inhibited the migration of human NK cells. Activation of AHR by its agonist FICZ induced ASB2-dependent filamin A degradation in NK cells; conversely, knockdown of endogenous ASB2 inhibited filamin A degradation. Reduction of filamin A increased the migration of primary NK cells and restored the invasion capacity of AHR-deficient NK cells. Our study introduces AHR as a new regulator of NK cell migration, through an AHR-ASB2-filamin A axis and provides insight into a potential therapeutic target for NK cell-based immunotherapies.